Awareness and Constraints Regarding Water Conservation Practices in Haryana (India) - Kumar, Pawan; Mukteshawar, Rati; Rani, Sonia; Malik, J S; Kumar, Narender (Indian Journal of Extension Education, 2025)
Water and soil are the most important inputs essential for crops. Both shortage and excess of water affects the growth and development of the plants, yields and quality of produce. There are numerous methods to reduce such losses and to improve soil moisture like mulching, cropping pattern, planting of trees and water harvesting etc. The study was carried out in two agro-climatic zone i.e. north-eastern zone and south-western zone of Haryana state. A total 240 farmers were interviewed with well-structured interview schedule for awareness and constraints regarding water conservation practices. The findings revealed that farmers’ had high awareness about ‘canal water is best for crops’, ‘nearness of soil and water testing laboratory’ and ‘water harvesting reduce soil erosion’. The major constraints reported by farmers were ‘Lack of soil and water testing facilities and delay in reports’ and ‘Deterioration of water quality in indigenous water harvesting structure’.